Comparative study for Utilization of machines in the Flow-Shop Scheduling Problems (Journal of Basic and Applied Research in Biomedicine, 2022)
Scheduling is the procedure of generating the schedule which is a physical document and generally informs the happening of things and demonstrate a plan for the timing of certain activities. The flow shop problem is one of the most widely studied classical scheduling problems and reflects real operation of several industries. The aim of the present work is to evaluate the performance of four methods when it is used to solve flow shop scheduling problems with minimization makespan. The four heuristics methods are Johnson, Palmer, CDS and Gupta methods. In this work, an attempt has been made to solve the flow shop scheduling problem for comparative study for utilization of machines in the flow-shop scheduling problems among pervious methods.  A simulation study has been made to evaluate the performance of the four method under consideration based on two performance measures  makespan and utilization of machine , the results has been proved  that the Palmer and CDS heuristic methods show the minimum value of average of makespan and average utilization of machine  when it compared with other heuristic methods.